Effect of hydrogen-diesel dual-fuel usage on performance, emissions and diesel combustion in diesel engines - Karagoz, Yasin; Sandalci, Tarkan; Yuksek, Levent; Dalkilic, Ahmet Selim; Wongwises, Somchai (SAGE PUBLICATIONS LTD, 2016)
Diesel engines are inevitable parts of our daily life and will be in the future. Expensive after-treatment technologies to fulfil normative legislations about the harmful tail-pipe emissions and fuel price increase in recent years created expectations from researchers for alternative fuel applications on diesel engines. This study investigates hydrogen as additive fuel in diesel engines. Hydrogen was introduced into intake manifold using gas injectors as additive fuel in gaseous form and also diesel fuel was injected into cylinder by diesel injector and used as igniter. Energy content of introduced hydrogen was set to 0%, 25% and 50% of total fuel energy, where the 0% references neat diesel operation without hydrogen injection. Test conditions were set to full load at 750, 900, 1100, 1400, 1750 and finally 2100 r/min engine speed. Variation in engine performance, emissions and combustion characteristics with hydrogen addition was investigated. Hydrogen introduction into the engine by 25% and 50% of total charge energy reveals significant decrease in smoke emissions while dramatic increase in nitrogen oxides. With increasing hydrogen content, a slight rise is observed in total unburned hydrocarbons although CO2 and CO gaseous emissions reduced considerably. Maximum in-cylinder gas pressure and rate of heat release peak values raised with hydrogen fraction.
Keywords: Hydrogen; diesel engine; smoke; NOx; rate of heat release; INJECTION; IGNITION; GAS; MIXTURES; Thermodynamics; Engineering